The Dynamics of Product Naming Processes for Micro, Small, and Medium Enterprises (MSME) in Kotakulon Village - Nurhasanah, Nurhasanah; Devita, Afni Apriliyanti; Adi, Soni Rahayu; Lesmana, Yogi Wijaya (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2024)
This study aims to investigate the dynamics of the MSME product naming process in Kotakulon Village and analyze the role of names in shaping the brand image. The study used ethnolinguistics analysis combined with a qualitative descriptive method to determine the dynamic of the naming process. Ethnolinguistics theory was used to solve the research questions: (1) how is the product naming process, and (2) what is the background behind the product naming process? The experts and the owner of the MSME product were contacted for observations, interviews, and documentation to gather data. The results show that the dynamic of the product naming process has eight categories. Those are processed product name, original product name, local language product name, acronym product name, local product name, shape characteristics product name, unique product name, and owner’s product name. The study concludes that MSME owners should know the importance of brand image. The benefit is that it will make the product better known to the public and make consumers repurchase it.